Use of surgical lasers in small animal dermatology. Issue 3 (31st March 2023) - Pieper, Jason
Abstract : Background: Use of lasers in veterinary medicine has significantly increased over the past decade. What was once a piece of equipment, almost exclusively used by veterinary specialists, has now become a common piece of equipment in general veterinary practices. It is imperative to know the appropriate situations and diseases for which lasers can be used. Aim of the article: This article covers the basics of lasers, including discussion of both diode and CO2 lasers. It also discusses several skin diseases and/or conditions in which lasers are commonly used.